Photoresponsive smectic liquid crystalline multipods and hyperbranched azo polymers - Nardele, Chinmay G.; Asha, S. K. (Journal of Physical Chemistry B, 2014)
Liquid crystalline azobenzene containing triped and tetraped monomers were designed and synthesized and further used as B-3 and B-4 type monomers to form hyperbranched polymers with tetraethylene glycol as the A(2) type comonomer. The mesophase characteristics of the multiarm-star mesogens and hyperbranched polymers were analyzed using various instrumentation techniques like differential scanning calorimetry (DSC), polarized light microscopy (PLM) and variable temperature XRD. The multipod monomers as well as hyperbranched polymers exhibited thermotropic smectic liquid crystalline characteristics with a tendency toward higher ordered smectic LC phases with increased branching. The hyperbranched polymers exhibited lamellar organization even in the as-solvent precipitated powder sample indicating higher extent of nanosegregation. Their potential application as fast switching photochromic materials was highlighted by carrying out isothermal photo-switching experiments in the LC state. Reversible isothermal smectic-isotropic phase transition could be achieved by UV irradiation in <1 s in the multipod monomers, while it required >2 s UV irradiation in the case of the hyperbranched polymers.